RACARP: a robustness aware routing protocol for cognitive radio ad hoc networks - Che-Aron, Zamree; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Hassan, Wan Haslina; Rahman, Md. Arafatur (Little Lion Scientific Islamabad Pakistan, 2015)
t:Cognitive Radio (CR) is a new paradigm which offers a viable solution to deal with the spectrum shortage problem and enhances the spectrum utilization in wireless communication systems. In Cognitive Radio Ad Hoc Networks (CRAHNs), data routing is one of the most challenging tasks due to varying link-quality, frequent topology changes and intermittent connectivity caused by the activities of Primary Users (PUs). This paper proposes a robustness aware routing protocol for CRAHNs, referred to the Robustness Aware Cognitive Ad-hoc Routing Protocol (RACARP), with an aim to provide robust transmission path and offer fast route recovery in presence of PU activities during data delivery. The Expected Path Delay (EPD) routing metric used in the protocol for path decision is also introduced. The protocol avoids creating a transmission path that uses PU’s channel in PU regions in order to counteract the impact of PU activity. Moreover, for the purpose of fast route recovery, the multi-path multi-channel routes are given by utilizing the joint path and spectrum diversity in routing. The performance evaluations are conducted through simulations using NS-2 simulator. The simulation results obviously demonstrate that the RACARP protocol can significantly achieve better performance in terms of average throughput, packet loss, average end-to-end delay, and average jitter as compared to the recently proposed D2CARP protocol in identical scenarios